Biological tank process optimization and operation control system and control method thereof - SUN YUEDI; WEI SHANGYANG; BI CHUANYA (2017)
The invention discloses a biological tank process optimization and operation control system which comprises an intelligent biological process optimization and dynamic course control system, an SCADA/DCS (supervisory control and data acquisition/distribute control system) and an execution mechanism, wherein the intelligent biological process optimization and dynamic course control system is responsible for on-line course control on dynamic conditions and non-linear variation characteristics of fed water and microorganism activities of a sewage plant, and is used for providing process operation parameters after the dynamic condition optimization as target control values to a biological tank control system in real time; the SCADA/DCS is used for transmitting monitoring data to the intelligent biological process optimization and dynamic course control system, used for receiving data calculated and processed by using the intelligent biological process optimization and dynamic course control system, and used for co